Colorectal endoscopic submucosal dissection using the pocket-creation method with single clip traction: a feasibility study - Nomura, Tatsuma; Hayashi, Yoshikazu; Morikawa, Takaaki; Okada, Masahiro; Fukuda, Hisashi; Takezawa, Takahito; Sunada, Keijiro; Lefor, Alan Kawarai; Yamamoto, Hironori (Endoscopy International Open, 2021)
Background and study aims The pocket-creation method (PCM) facilitates dissection of the central part of a tumor. We previously developed the PCM with clip traction (PCM-CT) to facilitate opening the mucosal pocket, which otherwise could become cumbersome. In the present study, we aimed to examine the feasibility of PCM-CT for colorectal endoscopic submucosal dissection (ESD).Patients and methods PCM-CT was performed on 30 patients with early colorectal tumors from October 2019 to April 2020. PCM-CT allows efficient opening of the mucosal pocket by using the PCM to dissect the center of the lesion and then apply traction with a single clip after making a circumferential mucosal incision.Results The median specimen major axis length, ESD time, ESD speed, and en bloc resection rate were 48 mm, 84 minutes, 20 mm2/min, and 100 % (30/30), respectively. The success rates for the traction clip and median single-clip-traction time were 100 % (30/30) and 1.5 minutes, respectively.Conclusions Colorectal ESD using PCM-CT is a simple and promising method.